Effects of Serial Passage on the Characteristics and Cardiac and Neural Differentiation of Human Umbilical Cord Wharton’s Jelly-Derived Mesenchymal Stem Cells - Jianchun Lian; Shijie Lv; Chang Liu; Yang Liu; Shujun Wang; Xin Guo; Feng Nan; Hua Yu; Xin He; Guangwei Sun; Xiaojun Ma (Stem Cells International)
Background and Objective. It is important to guarantee the quality of stem cells. Serial passage is the main approach to expand stem cells. This study evaluated effects of serial passage on the biological characteristics of human umbilical cord Wharton’s jelly-derived MSCs (WJ MSCs). Methods. Biological properties of WJ MSCs in the early (less than 10 passages, P10), middle (P11–20), and late (more than P20) phases including cell proliferation, cell cycle, phenotype, senescence, oncogene expression, stemness marker expression, and differentiation capacity were evaluated using flow cytometry, real-time PCR, immunocytofluorescence, and western blot. Results. It was found that there were no significant differences in cell proliferation, cell cycle, phenotype, and stemness marker expression in different phases. However, the expression of senescence-related gene, p21, and oncogene, c-Myc, was significantly upregulated in the late phase, which had close relations with the obviously increased cell senescence. Moreover, cardiac differentiation capability of WJ MSCs decreased whereas the propensity for neural differentiation increased significantly in the middle phase. Conclusions. This study reveals that WJ MSCs in the early and middle phases are relatively stable, and effect of serial passage on the lineage-specific differentiation should be considered carefully.